Sexual behavior of married young women: A preliminary study from north India - Avasthi Ajit; Kaur Rajinder; Prakash Om; Banerjee Anindya; Kumar Lata; Kulhara P (Wolters Kluwer Medknow Publications, 2008)
Background: There are significant gaps in the scientific literature concerning female sexual behavior and attitudes surrounding sexuality, which have definitive implications on public health and clinical work. Aim: To study the sexual behavior of young married Indian women. Materials and Methods: The study group comprised 100 consecutive women attending the Department of Pediatrics for the care of noncritical children in a multispecialty, tertiary care teaching hospital setting in North India. Current levels of sexual functioning and satisfaction were assessed by using the Brief Index of Sexual Functioning for Women (BISF-W). All participants were also administered a translated and culturally adapted instrument called Sex Knowledge and Attitude Questionnaire-II (SKAQ-II). Results: Peno-vaginal sex continues to be considered the most desired and actually performed sexual activity for arousal and orgasm, followed by kissing and foreplay. Difficulties while performing sexual activity, in the form of physical problems, were faced by 17% of the participants. The participants displayed adequate sexual knowledge and favorable attitude towards sexuality as measured by SKAQ-II. Conclusion: The present study is a preliminary effort to understand the contemporary female sexual behavior, knowledge and attitude by employing standard instruments. Still further studies are required in this area.